KESANTUNAN BERBAHASA DALAM NOVEL GEMARIEL KARYA RIMA HIDAYATUL AENI - Sutardi; Liizzah Diyanatul Manzil (Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to examine the politeness in language found in the novel Gemariel by Rima Hidayatul Aeni. The analysis is based on Leech's six principles of politeness, namely the maxims of tact, generosity, approbation, modesty, agreement, and sympathy. The research method used is descriptive qualitative. The research data consist of the utterances of characters in the novel Gemariel. The data source is the novel Gemariel by Rima Hidayatul Aeni, which comprises 280 pages and was published by PT Sembilan Cahaya Abadi in January 2023. The data collection technique employed is observation and note-taking. The results show that 42 utterances containing the principles of politeness were identified, with the following details: (1) 8 utterances containing the maxim of tact, (2) 6 utterances containing the maxim of generosity, (3) 15 utterances containing the maxim of approbation, (4) 4 utterances containing the maxim of modesty, (5) 7 utterances containing the maxim of agreement, and (6) 2 utterances containing the maxim of sympathy.